2022
DOI: 10.1111/tid.13783
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor multidrug‐resistant organisms on solid organ transplant recipient outcomes

Abstract: Background:The impact of donor colonization or infection with multidrug-resistant organisms (MDROs) on solid organ transplant (SOT) recipient outcomes remains uncertain. We thus evaluated the association between donor MDROs and risk of posttransplant infection, graft failure, and mortality.Methods: A multicenter retrospective cohort study was performed. All SOT recipients with a local deceased donor were included. The cohort was divided into three exposure groups: recipients whose donors had (1) an MDRO, (2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Cystic fibrosis (CF) patients awaiting lung transplant have high rates of MDR Pseudomonas and Mycobacterium abscessus, whilst many centres list the presence of Burkholderia cepacia complex as a contraindication to lung transplant [19][20][21]. The presence of MDROs is associated with worse illness [22] and increased mortality while awaiting transplant, but there are mixed reports of changes in posttransplant outcomes [23][24][25][26][27].…”
Section: Multidrug-resistant Infections In Transplant Recipientsmentioning
confidence: 99%
“…Cystic fibrosis (CF) patients awaiting lung transplant have high rates of MDR Pseudomonas and Mycobacterium abscessus, whilst many centres list the presence of Burkholderia cepacia complex as a contraindication to lung transplant [19][20][21]. The presence of MDROs is associated with worse illness [22] and increased mortality while awaiting transplant, but there are mixed reports of changes in posttransplant outcomes [23][24][25][26][27].…”
Section: Multidrug-resistant Infections In Transplant Recipientsmentioning
confidence: 99%
“…Risk factors for developing post‐transplant ESBL‐E infection include previous antibiotic exposure, pre‐transplant colonization, perioperative prophylaxis, prolonged tracheal intubation, long‐term hospitalization, urinary tract obstruction and instrumentation, kidney‐pancreas transplantation, post‐transplant renal replacement therapy (RRT), and recurrent urinary tract infection (UTI), as reviewed elsewhere 3,19 . A recent multicenter case‐control study in the USA comprising 988 ESBL‐E BSI episodes identified various risk factors of relevance, including the isolation of ESBL‐E in a prior culture, a corticosteroid‐containing immunosuppression regimen, acute rejection treated with corticosteroids, and previous exposure to third‐generation cephalosporins, echinocandins and trimethoprim‐sulfamethoxazole 20 …”
Section: Esbl‐e Infections After Sot: Epidemiology Molecular Characte...mentioning
confidence: 99%
“…One factor which may contribute to MDRO DDI overall is the limited availability of donor culture data at the time of organ recovery. In this context, standard perioperative prophylaxis at the time of transplantation has limited activity against the majority of MDROs, apart from MRSA when vancomycin is administered [23 ▪ ]. Additionally, prompt communication of donor culture results is imperative, and it is unclear to what degree communication delays may have contributed to transmissions in the above reports.…”
Section: Epidemiology Of Multidrug-resistant Organism Donor-derived I...mentioning
confidence: 99%